المدَائِحُ النَّبَوِيَّةُ بَيْنَ الشِّعْرِ والنَّثْرِ - مرزوق, أبو بكر; بن بوزيد, أحمد (جامعة الوادي - university of Eloued, 2022)
لقد شاع من أدب المدائح النّبوية ما كُتب (شِعرا)، حيث زخر الأدب المرتبط بشخص رسول الله صلّى الله عليه وسلّم وشخصيّته العظيمة بكَمٍّ هائلٍ من الأشعار، هي ظلّ أدب السّيرة النّبوية، و غاب ما كُتِب (نثرا) من خطب ومواعظ ورسائل وقصص وأوصاف ارتبطت كلها بمدحه صلّى الله عليه وسلّم والتي تميزت ببنية خاصّة ودلالات كذلك, فمن الجليل والجميل التّعرّف إلى حقيقة هذا التّراث المدْحِيّ العريق والمغيَّب عن المدح، وكيفية الاستفادة منه, مع فتح المجال لدراسته والبحث فيه. Abstract; The most known for the literature of religious praise is what was written as odes in poetry. Since his birth, the prophet Mohammed Peace Be Upon Him, and throughout the history, the Arab-Islamic literature was replete with an important literary works related to the character of the prophet peace be upon him and his great personality, which is the shadow of the Prophet’s biography literature , and the poetry that circulated in its oracle. What was written (in prose) including religious speech, sermons, letters, stories and descriptions were all related to the praise of the prophet peace be upon him , and which were distinguished by a special structure and connotations . It is great to get acquainted with the truth of this praiseworthy ancient heritage and how to make its conscious use as an investigation and investment as a field of study and research.
مقال
Keywords: المدائح النبوية ؛ المولد النبوي ؛المولديات ؛ الموالد؛ المدائح النثرية; Prophetic Praises; Birth of the Prophet; Moulidiate ; Births;Prophetic praise (odes).